1997
DOI: 10.1083/jcb.136.4.919
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between Adherens Junctions and Desmosomes Depends on Plakoglobin

Abstract: Squamous epithelial cells have both adherens junctions and desmosomes. The ability of these cells to organize the desmosomal proteins into a functional structure depends upon their ability first to organize an adherens junction. Since the adherens junction and the desmosome are separate structures with different molecular make up, it is not immediately obvious why formation of an adherens junction is a prerequisite for the formation of a desmosome. The adherens junction is composed of a transmembrane classical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
222
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(235 citation statements)
references
References 51 publications
12
222
1
Order By: Relevance
“…Conditions are less clear in the E-cadherin system. Here, there is no direct contact with the keratin filaments; however, the desmosomes may be influenced via plakoglobin, which is a component of both systems (30). Then, mediated by plakoglobin, the reorganizing force of the keratin filaments could extend via the desmosomes into the zonula adherens.…”
Section: Discussionmentioning
confidence: 99%
“…Conditions are less clear in the E-cadherin system. Here, there is no direct contact with the keratin filaments; however, the desmosomes may be influenced via plakoglobin, which is a component of both systems (30). Then, mediated by plakoglobin, the reorganizing force of the keratin filaments could extend via the desmosomes into the zonula adherens.…”
Section: Discussionmentioning
confidence: 99%
“…A431D cells are a derivative of A431 cells that have lost expression of the classical cadherins (Eand P-cadherin) and are unable to assemble adherens junctions and desmosomes (Lewis et al 1997). Previous work in our laboratory has demonstrated that expression of many classical cadherins in A431D cells will support junction assembly (data not shown).…”
Section: Mutant Plakophilin-2 Is Unable To Initiate Desmosome Assemblymentioning
confidence: 99%
“…A431 cells express classical cadherins (E-and P-cadherin) and assemble fully functional adherens junctions and desmosomes. A431D cells are a cadherin-negative derivative of A431 cells in which classical cadherin expression is lost and these cells do not assemble cell junctions (Lewis et al 1997). Desmosome assembly is restored in A431D cells by expressing a classical cadherin and plakophilin (Wahl 2005).…”
Section: Cell Culturementioning
confidence: 99%
“…β-Catenin also functions as a bridge between the cytoplasmic domain of cadherins and the actin-containing cytoskeleton [25,26]. β-Catenin complex with the cytoplasmic tail of Ecadherin is mostly regulated by phosphorylation at tyrosine-654, which induces β-catenin dissociation from E-cadherin, thus negatively influencing cell-cell adhesion [27].…”
Section: Introductionmentioning
confidence: 99%